Measuring Animal Age with DNA Methylation: From Humans to Wild Animals - De Paoli-Iseppi, Ricardo; Deagle, Bruce E.; McMahon, Clive R.; Hindell, Mark A.; Dickinson, Joanne L.; Jarman, Simon N. (Frontiers in Genetics, 2017)
DNA methylation (DNAm) is a key mechanism for regulating gene expression in animals and levels are known to change with age. Recent studies have used DNAm changes as a biomarker to estimate chronological age in humans and these techniques are now also being applied to domestic and wild animals. Animal age is widely used to track ongoing changes in ecosystems, however chronological age information is often unavailable for wild animals. An ability to estimate age would lead to improved monitoring of (i) population trends and status and (ii) demographic properties such as age structure and reproductive performance. Recent studies have revealed examples of DNAm age association in several new species increasing the potential for developing DNAm age biomarkers for a broad range of wild animals. Emerging technologies for measuring DNAm will also enhance our ability to study age-related DNAm changes and to develop new molecular age biomarkers.